2019
DOI: 10.1371/journal.pone.0219208
|View full text |Cite
|
Sign up to set email alerts
|

LC-ESI/MS/MS analysis of neonicotinoids in urine of very low birth weight infants at birth

Abstract: Objectives Neonicotinoid insecticides are widely used systemic pesticides with nicotinic acetylcholine receptor agonist activity that are a concern as environmental pollutants. Neonicotinoids in humans and the environment have been widely reported, but few studies have examined their presence in fetuses and newborns. The objective of this study is to determine exposure to neonicotinoids and metabolites in very low birth weight (VLBW) infants. Methods An analytical metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…To date, most neonicotinoid uses are (or are planned to be) suspended in Europe, with the exception of acetamiprid. Here, it is interesting to note that acetamiprid appeared one of the less toxic neonicotinoids for pollinators, but it is one of the most worrying neonicotinoids for human health (Ichikawa et al 2019).…”
Section: Regulations and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most neonicotinoid uses are (or are planned to be) suspended in Europe, with the exception of acetamiprid. Here, it is interesting to note that acetamiprid appeared one of the less toxic neonicotinoids for pollinators, but it is one of the most worrying neonicotinoids for human health (Ichikawa et al 2019).…”
Section: Regulations and Conclusionmentioning
confidence: 99%
“…Hallmann et al 2017;Krupke and Tooker 2020;Pelosi et al 2020;Ewere et al 2021) but affects also vertebrates, directly or indirectly (Paquet-Walsh et al 2019;Eng et al 2019). In addition, there is also growing pieces of evidence that mammals (including humans) can be directly affected by these insecticides (Taira 2014;Cimino et al 2016;Caron-Beaudoin et al 2017;Wang et al 2017;Berheim et al 2019;Ospina et al 2019;Ichikawa et al 2019;Wang et al 2020;Thompson et al 2020;Oya et al 2020;Bonmatin et al 2020); this in sharp opposition to what was expected at the time of their registration.…”
Section: Regulations and Conclusionmentioning
confidence: 99%
“…While daily intakes are below the current chronic reference doses, concern is raised over the health risk of neonicotinoids to children via dietary exposure due to their increased use and ubiquitous presence in fruits and vegetables. -Ichikawa et al (2019) report the first evidence worldwide of neonicotinoid exposure in new born babies in the early phase after birth, suggesting a need to examine potential neurodevelopmental toxicity of neonicotinoids and metabolites in human foetuses. -Becker et al (2020) found that selection pressure from contamination by imidacloprid (and diazinon) caused insensitive snails to dominate over their less tolerant competitors, increasing a pathway for transmission of Schistosomiasis.…”
Section: Human Exposurementioning
confidence: 99%
“…Both overall reliance on pesticides relative to other pest-management tools, and the number and diversity of residues in diets have risen steadily for decades. The world's most widely used herbicide (glyphosate) and heavily applied family of insecticides (neonicotinoids) are routinely detected in human urine [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%